Research Needs in the Companies of the City of Quito on Productive Processes of Goods and Services - Barreno Benavides, Luis (2013)
Growth and economic development of a country is closely related to the quality of the various higher education institutions responsible for preparing and training professionals in the different areas of knowledge for application of their knowledge in the productive sectors of goods and services , a situation requiring the University to be in constant contact with the business sector, in order to capture the needs of deve1opment of research, aimed at technology innovation to improve their yield and thereby improve their products by reducing their production costs and increasing their profitability. This reason is important enough to conduct this investigation. The research has made taking as a source of statistical information database of the Superintendency of Companie, in which the names of existing companies by type of activity is recorded in the city of Quito, which was combined with research field through interviews and survey application managers and managers in the areas of production of goods or services of those companies. The results achieved from the research were very important, as it allowed us to know, what are the research questions that need to develop to their fields of productive organizations and universities would be able to bid.